Prevalence and risk factors of fasciolosis in a bovine population from farms in Taiping, Malaysia - Che-Kamaruddin, Naim; Hamid, Nur Fazila Saulol; Idris, Lokman Hakim; Yusuff, Ferdaus Mohamat; Ashaari, Zulfa Hanan; Yahaya, Hasmawati; Sahimin, Norhidayu; Isa, Nur Mahiza Md (Elsevier, 2024)
Fasciolosis is a zoonotic disease, considered an emerging neglected tropical disease threatening ruminant productivity and causing economic losses. Controlling fasciolosis is challenging due to the complex life cycle of Fasciola, which involves snail intermediate hosts. The high rainfall status in Taiping makes it an optimal region for snail abundance, which increases the opportunity to complete Fasciola's life cycle. Previous studies showed that liver condemnation caused by fasciolosis was highly prevalent in the Taiping abattoir compared to other investigated main abattoirs of Peninsular Malaysia. Therefore, the present study determined the prevalence of bovine fasciolosis and risk factors in farms from Larut and Matang (Taiping), Malaysia. Sampling was carried out from February until August 2020. In this cross-sectional study, a total of 371 fecal samples from bovines (dairy cattle, beef cattle, buffalo) were examined from 23 farms selected based on location, farmer consent, and history of anthelmintic usage. Animal's intrinsic and farm management details were recorded, and interview sessions were conducted with farmers to collect information on the potential risk factors. Individual fecal samples were examined for the presence of Fasciola egg using Flukefinder® sedimentation. There was moderate prevalence of bovine fasciolosis in Taiping (36.9%, n = 137/371). Significant risk factors (p < 0.05) were observed, which include buffalo group (OR = 9.5, 95% CI: 9.44–9.55), age of >3 years (OR = 5.5, 95% CI: 5.43–5.57), thinner animals with body condition score of 1 to 4 (OR = 1.2–14.9, 95% CI: 1.09–15.08), and larger grazing area (OR = 1.3, 95% CI: 1.30–1.31). Additional risk factors include the presence of more than one ruminant species in the same farm (OR = 2.0–2.1, 95% CI: 2.00–2.22), extensive housing system (OR = 4.0, 95% CI: 3.77–4.23), farm age (OR = 1.2, 95% CI: 1.20–1.21), and also co-infection with Paramphistomes (OR = 1.4, 95% CI: 1.10–1.71). The present study underscores the importance of local bovine fasciolosis epidemiology, which could be used to conduct future veterinary and public health programmes to inform effective parasitic management aimed at reducing the prevalence of fasciolosis.